NEW GEOECONOMIC STRATEGIES AND THE ROLE OF THE G20: ELEMENTS FOR BRAZIL’S ROLE - Giorgio Romano Schutte; Diego Araujo Azzi (Revista Tempo do Mundo)
This article analyzes the challenges faced by the Group of Twenty (G20) in light of the recent trends of deglobalization, geopolitical tensions, and geoeconomic fragmentation. It argues that the recent combined dilemmas of security and defense, obstacles to peace, and economic-trade coordination between nations represent a new phase for the group. Paradoxically, in addition to restrictions on more cooperative action, the new context also represents opportunities for renewed Brazilian action in the G20 amid the current reconfiguration of international relations.